CHANGES IN PSYCHOLOGICAL AND EMOTIONAL STATE OF PULMONARY TUBERCULOSIS CHANGES WITH ANTI-TUBERCULOSIS CHEMOTHERAPY ACCOMPANIED BY PSYCHOLOGICAL SUPPORT - G. V. Baranova; N. V. Zolotova; V. V. Strel'tsov; N. Yu. Kharitonova; A. A. Akhtyamova; I. A. Vasilieva (Туберкулез и болезни лёгких, 2016)
The article describes the investigation of psychological and emotional state of pulmonary tuberculosis patients belonging to various categories having in-patient treatment. The patients who referred to the psychologist for help while having anti-tuberculosis treatment manifested worse psychological dysfunctions compared to the patients who did not require psychological care. After psychological counseling the  patients manifested less destructive behavior and  psychological problems and  the  increase in  the  life quality as per the number of various scores. The positive changes in psychological state of the patients from the main group were confirmed by the elimination of the preceding confident di`erences in rates compared to the patients from comparison group regarding certain parameters of nervous psychological stability. Psychological support during pulmonary tuberculosis treatment is one of substantial tools of treatment e_ciency enhancement.